Upaya Penguatan Literasi Anak Usia Dini melalui GERDASI - Desty Putri Hanifah; Rochyani Lestiyanawati (Jurusan Ilmu Pendidikan - Universitas Lampung, 2023)
This activity aimed to strengthen the literacy movement in early childhood through the habit of reading aloud at school and home. Gerdasi was a series of literacy-strengthening programs implemented at Kindergarten/RA Al Hidayah in the form of reading aloud at school and socializing the selection of children's books for parents. Gerdasi was held in April-June 2023 and attended by all children and parents/guardians of Kindergarten/RA Al Hidayah. The stages of implementing the community service activities included: 1) laying the foundation; 2) research design; 3) data gathering and analysis; and 4) acting on findings. Based on observations during reading-aloud activities, the data showed that more than 90% of children liked reading-aloud activities and enjoyed every discussion process. However, children's interest in books is not facilitated well at home. These findings became the basis for carrying out follow-up efforts in the form of socializing the selection of children's books with parents/guardians as the target. This socialization explained important points about literacy facts, choosing good children's books, as well as alternatives for choosing e-books. It was hoped that parents' knowledge regarding sites that provide e-books for children's storybooks could be an inspiration for parents to provide children with affordable reading materials